Inhibitory Effect of Plantago Major Extract on Biofilm Formation by Enterococcus faecalis from Teeth Infections - Modher, Mawj Numan; Mohanad, sarah; Alshanon, AhmedFadhel; Hussein, Sarmed Mohammed; Raheem, Yousif Shaker (American Journal of Biology and Natural Sciences, 2025)
Due to the pathogen’s resistance to conventional antibiotics, the potential of Plantago major, a medicinal herb with known antibacterial and anti-inflammatory properties, was evaluated as an alternative treatment. The current study aimed to assess the antibacterial efficacy of an extract of P. major leaves against Enterococcus faecalis isolated from teeth infections. E. faecalis isolates from infected root canals were tested for biofilm-forming ability using the 96-well microtiter plate assay. Antibiotic susceptibility was assessed using standard disc diffusion testing. The antibacterial and anti-biofilm activities of P. major extract were evaluated through disc diffusion and microdilution assays to determine inhibition zones and minimum inhibitory concentrations (MIC). Among the isolates, 29.5% were strong biofilm producers, 40% moderate, and 30.5% weak. The P. major extract exhibited inhibition zones ranging from 9 to 22 mm. MIC values 128 µg/mL. Most isolates were resistant to erythromycin, clindamycin, trimethoprim, and tetracycline, while imipenem remained effective. Biofilm formation was effectively reduced at all tested concentrations, with the greatest inhibitory effect observed at a concentration of 500 mg/mL. Plantago major extract demonstrated antibacterial and anti-biofilm activity against multidrug-resistant E. faecalis. These findings suggest its potential as a complementary therapeutic agent in managing persistent root canal infections.